Arterial Stiffness Is Reduced Regardless of Exercise Training in Obese Paediatric Populations: A Meta-Analysis of Randomised Controlled Trials - Garcia-Hermoso, A (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Sin Resumen Disponible